Shifting gears: Study of immune system parameters of male habitual marathon runners - Panagoulias, Ioannis; Charokopos, Nikolaos; Thomas, Iason; Spantidea, Panagiota I.; de Lastic, Anne-Lise; Rodi, Maria; Anastasopoulou, Spyridoula; Aggeletopoulou, Ioanna; Lazaris, Charalampos; Karkoulias, Kiriakos; Leonidou, Lydia; Georgopoulos, Neoklis A.; et al. (Frontiers in Immunology, 2023)
Aim: Marathon is a running event in which athletes must cover a distance of 42.195 km. In addition to participating in marathons, marathoners have incorporated extensive running into their lifestyle. In the present study, we investigated the effect of long-term strenuous exercise in the form of marathon running on the immune system. Methods & Results: We collected peripheral blood samples from 37 male marathoners before/after a race and 37 age/sex/body mass index (BMI)-matched healthy sedentary controls. Hematological and biochemical tests revealed race-induced leukocytosis attributable to neutrophilia and significant increases in plasma lactate dehydrogenase (LDH), creatine phosphokinase (CPK), and cortisol concentrations. Phenotypic analysis of lymphocytes revealed race-induced significant decrease in the number of lymphocytes, memory helper T (Th) cells, naive, memory and activated cytotoxic T (Tc) cells, natural killer (NK), NKT, and B1 cells, and a significant increase in the number of activated Th and regulatory Th cells (Tregs). Compared with controls, marathoners maintained significantly lower levels of memory and activated Th cells and higher levels of activated Tc and B1 cells. Measurement of plasma cytokine levels revealed a pro-inflammatory cytokine polarization that increased after the race. Examination of gene expression of cytokines and Th-cell signature transcription factors in peripheral blood mononuclear cells revealed a significant decrease in tumor necrosis factor α (TNF-α) and interleukin (IL)-17, and a significant increase in IL-6, IL-10 and forkhead box P3 (FoxP3) after the race. Compared with controls, marathoners maintained significantly higher levels of TNF-α. Assessment of the suppressive capacity of Tregs in co-cultures of isolated effector Th cells and Tregs showed significantly increased suppressive capacity of marathoners’ Tregs after the race. Conclusions: Compared with controls, marathoners live with permanent changes in certain immune parameters. Marathoners exhibit a stable pro-inflammatory cytokine polarization that increases after the race and is counterbalanced by increased numbers of Tregs overexpressing FoxP3 and having increased suppressive capacity.